Globally recognised UMP Confucius Institute offers Mandarin learning for community benefit - Mimi Rabita, Abdul Wahit (UMPSA, 2023)
BEIJING, CHINA, 21 July 2023 - The Joint Conference of Southeast Asian Confucius Institutes 2023 in Beijing, China successfully gathered 300 representatives of the Confucius Institute (CI) from ten countries in Southeast Asia.